Influence of pretreatment methods on the sorption capacity of carbon nanotubes - Abdul Majid, Zaiton (2005)
The effect of pretreatment methods on the hydrogen sorption capacity was carried out using commercial multiwall nanotubcs (MWNT). The hydrogen sorption characteristics of M\VNT were investigated by means of a Temperature-Programmed Desorption (TPD), BET surface area measurement and Scanning Electron Microscopy (SENT). Hydrogen adsorption and desorption was carried out at room temperature. The samples were subjected to thermal and acid pretreatment methods. Thermal treatment involved heating the MWNT at 350 C for 3 hours. Acid treatment was carried out under 2 conditions i.e. refluxing in nitric acid for a duration of 12 hours and refluxing in nitric acid for a duration of 4 hours followed by heating at 400 C for 4 hours. Hydrogen adsorption and desorption was carried out at room temperature. Results of the studies showed an increase in the BET surface area with pretreatment under nitric acid reflux followed by heating at 400 C showing about 30 % increase in surface area. The amount of H2 desorped is influenced by the pretreatment methods. MWNT which were pretreated by refluxing in nitric acid, followed by heat treatment showed the highest volume of hydrogen desorbed per gram sample. Studies also indicated a direct correlation between the amount of hydrogen desorped and surface area of the commercial MWNT. The enhanced surface area hydrogen sorption capacity is be due to the opening up of the MWNT ends removal of catalytic impuritics and amorphous carbon upon treating with nitric acid and further heat treatment.